Postictal switch in blood flow distribution and temporal lobe seizures. Issue 10 (October 1992) - Newton, M R; Berkovic, S F; Austin, M C; Rowe, C C; McKay, W J; Bladin, P F
Abstract : The ictal increase of regional cerebral blood flow has yet to be fully utilised in the investigation of focal seizures. Although single photon emission tomography (SPECT) is being increasingly used in the localisation of epileptic foci, the evolution and time courses of the peri-ictal perfusion changes have yet to be clarified. We performed serial SPECT studies in the interictal, ictal and immediate postictal states in 12 patients with refractory temporal lobe epilepsy to define the patterns and duration of peri-ictal cerebral blood flow changes. Visual analysis showed a constant pattern of unilateral global increases in temporal lobe perfusion during seizures which suddenly switched to a pattern of relative mesial temporal (hippocampal) hyperperfusion and lateral temporal hypoperfusion in the immediate postictal period. Quantitative analysis confirmed the visual assessment. Lateral temporal cortex ictal/normal side to side ratios were increased by mean 35.1% (95% confidence interval 21.8% to 48.4%) more in the ictal studies than in the interictal studies and mesial temporal cortex ratios increased by mean 30.8% (22.4% to 39.2%). In the postictal state, however, lateral temporal ratios were reduced by mean 7.7% (-15.8% to 0.4%) compared with interictal values, whereas mesial temporal perfusion was maintained compared with the interictal studies. These observations provide critical information for interpreting scans which can be used in the localisation of epileptic foci. This postictal switch in blood flow patterns may reflect the underlying metabolic processes of neuronal activation and recovery and have implications for understanding the neurobiology of human epileptic seizures.